Gambaran Hasil Pemeriksaan Tes Cepat Molekuler Mycrobacterium Tuberculosis di RSUD Tugu Jaya - Hamida, Indah; Yonita, Maria Regina Tri; Warsinah (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2025)
T Background : Tuberculosis (TB) remains a major public health problem worldwide, particularly in developing countries such as Indonesia. Early detection is essential in controlling TB transmission. Method : This study aimed to describe the results of pulmonary TB examinations using the GeneXpert Molecular Rapid Test (TCM) method at RSUD Tugu Jaya. This research used a descriptive quantitative design with a total sampling technique, involving 400 patient samples. Pulmonary tuberculosis examination was performed using the GeneXpert rapid molecular test (TCM), which is based on an automated real-time PCR method. Results : The results showed that out of 400 patients, 353 (88.25%) were negative for TB, 46 (11.5%) were positive for Mycobacterium tuberculosis (MTB) with rifampicin sensitivity, and 1 (0.25%) was positive for MTB with rifampicin resistance. Age distribution revealed that the productive age group (15–50 years) had more active TB cases than other groups. Based on gender, males showed a higher proportion of TB cases than females. Conclusion : In conclusion, the GeneXpert TCM method is effective in detecting pulmonary TB, including drug-resistant TB, emphasizing the need for targeted preventive efforts in productive-age males. Keywords : Molecular Rapid Test, Mycobacterium tuberculosis, Pulmonary Tuberculosis